Phosphate conversion coating reduces the degradation rate and suppresses side effects of metallic magnesium implants in an animal model. Issue 6 (6th May 2016) - Rahim, Muhammad Imran; Tavares, Ana; Evertz, Florian; Kieke, Marc; Seitz, Jan‐Marten; Eifler, Rainer; Weizbauer, Andreas; Willbold, Elmar; Jürgen Maier, Hans; Glasmacher, Birgit; Behrens, Peter; Hauser, Hansjörg; et al.
Abstract: Magnesium alloys have promising mechanical and biological properties for the development of degradable implants. However, rapid implant corrosion and gas accumulations in tissue impede clinical applications. With time, the implant degradation rate is reduced by a highly biocompatible, phosphate‐containing corrosion layer. To circumvent initial side effects after implantation it was attempted to develop a simple in vitro procedure to generate a similarly protective phosphate corrosion layer. To this end magnesium samples were pre‐incubated in phosphate solutions. The resulting coating was well adherent during routine handling procedures. It completely suppressed the initial burst of corrosion and it reduced the average in vitro magnesium degradation rate over 56 days almost two‐fold. In a small animal model phosphate coatings on magnesium implants were highly biocompatible and abrogated the appearance of gas cavities in the tissue. After implantation, the phosphate coating was replaced by a layer with an elemental composition that was highly similar to the corrosion layer that had formed on plain magnesium implants. The data demonstrate that a simple pre‐treatment could improve clinically relevant properties of magnesium‐based implants. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1622–1635, 2017.